PENGARUH LANGSUNG DAN TIDAK LANGSUNG HUMAN CAPITAL TERHADAP NILAI PERUSAHAAN ( Studi Empiris terhadap Perusahaan Perbankan yang tercatat di Bursa Efek Indonesia periode 2010-2012 ) - Tresnasari, Fauzia; Juliarto, Agung (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to examine fundamental accounting variables and the role played by the components of intellectual capital including interaction between the components of intellectual capital in creating firm value. Fundamental accounting variables proxied by Book Value per Share (BVPS) and Earning per Share (EPS), while intellectual capital components as measured by Value Added Intellectual Coefficient (VAIC) consist of Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), and Structural Capital Efficiency (SCE). In addition, this research uses multiplication between HCE and SCE as an interaction variable. Research sample comprised all firms listed onÂ Indonesia Stock Exchange in the banking sector for the period 2010-2012. Sampling method used in this study was purposive sampling to obtain 84 observations for analysis. This study utilized Ordinary Least Square (OLS) regression as a main analysis technique. Findings confirm the existence of a positive relationship between fundamental accounting variables i.e. BVPS & EPS, andÂ firm value. Out of three components VAIC, only CEE shows positive relationship with firm value. The two components of IC, namely HCE and SCE, show a significant positive influence on firm value when these two variables interact. It indicates an indirect relationship between HC and firm value.